Elisabeth L. Engebretsen & William F. Schroeder (eds.): Queer/Tongzhi China. New Perspectives on Research, Activism and Media Cultures - Rydström, Jens (Tidsskriftet Antropologi, 2020)
Elisabeth L. Engebretsen & William F. Schroeder (eds.): Queer/Tongzhi China. New Perspectives on Research, Activism and Media Cultures Anmeldes af Jens Rydström